The Diel and Seasonal Heterogeneity of Carbonate Chemistry and Dissolved Oxygen in Three Types of Macroalgal Habitats - Li, Huiru; Moon, Hanbi; Kang, Eun Ju; Kim, Ja-Myung; Kim, Miok; Lee, Kitack; Kwak, Cheol-Woo; Kim, Haryun; Kim, Il-Nam; Park, Ki Yeol; Lee, Young Kweon; Jin, Ji Woong; et al. (Frontiers in Marine Science, 2022)
With growing concerns about ocean acidification, macroalgal communities is attracting more attentions because they contribute to seawater buffering capacity by altering coastal seawater biogeochemistry through their metabolisms. However, studies on diurnal and seasonal fluctuations in seawater chemistry within macroalgal communities are still rare. Here, we characterized the spatial and temporal heterogeneity in diurnal and seasonal dynamics of seawater carbonate chemistry and dissolved oxygen (DO) in three types of macroalgal habitats (UAM: ulvoid algal mat dominated, TAM: turf algal mat dominated, and SC: Sargassum horneri and coralline algae dominated). Our results showed that diurnal fluctuations in carbonate parameters and DO varied significantly among habitat types and seasons. Variations in carbonate chemistry and DO were affected by the intensity of photosynthesis and respiration and also by the physical processes. In particular, these parameters exhibited greater variations at the UAM habitat than the other habitats. Also, we demonstrated that macroalgal communities counteracted ocean acidification when ocean temperature befits macroalgae to do photosynthesis actively and thereby absorbed dissolved inorganic carbon. However, once temperatures exceeded the optimum ranges for macroalgae growth, respiration of the macroalgal communities began to take over photosynthesis and reversely increased CO2 concentrations. We concluded that the seawater carbonate chemistry was strongly influenced by the dominant metabolisms associated with the macroalgal habitat types, which may, in turn, alter their buffering capacity against ocean acidification.